University of South Florida St. Petersburg Student Research Journal, Vol. 2, Issue 1, article 2 : Geometric Probability of Mating Success for the Common Dog, Canis lupus familiaris - Jeffers, Mason (Digital Commons @ University of South Florida, 2012)
The common dog, Canis lupus familiaris, mates in the traditional dorsoventral mount position. Because neither the male nor the female can see their genitals during the dorsal-ventral mount, the geometric alignment of several physical factors must be accomplished for males to successfully delivery their sperm into the female's vagina. In this study, a conservative estimate of the random probability of mating success was calculated in the same way as one would calculate the random probability of a dart hitting the center of a target. One would determine the area of the bull's-eye, the female's vagina, relative to the area of the entire target, the female's posterior. A conservative estimate of the probability of random mating success for the common dog was 0.45% or at less than five chances out of a thousand. To increase the probability of mating success, the male and female must be of similar height; the male's shaft must be sufficiently long; the angle of erection must be sufficiently acute; and male's belly must be sufficiently lean to mount the female in such a way that his shaft is able to penetrate the female's vaginal canal.